EQUITY OFFERINGS’ INITIAL AND AFTERMARKET PRICE PERFORMANCE IN FINNISH EQUITY MARKET: Empirical Evidence from Finnish IPOs and SEOs from 1997–2002 - Sihvonen, Jukka (My University, 2005)
This study was to investigate if initial underpricing and aftermarket underperformance anomalies exist amongst Finnish unseasoned and seasoned equity offerings. Also cross-sectional returns analysis was conducted to examine, if some company-specific characteristic explain returns of offerings exceptionally well. Assembled data included 48 IPOs and 26 SEOs from years 1997–2002. Returns were adjusted with HEX portfolio index. Initial returns and 3-, 6-, 12- and 24-month aftermarket performance was analyzed. Statistical significance of results was tested with Student’s t-test. Cross-sectional patterns were analyzed with categorized portfolios and regression analysis. Significant conditional price trends were found. IPOs were underpriced 10,9 %, underperforming 2,4% to benchmark index after two years of aftermarket. SEOs were also underpriced 3,2%, but not significantly. SEOs underperformed 7,1% after two years of aftermarket. Industry, firm age and net sales were statistically significant explanatory variables for returns.
Keywords: Initial public offering; seasonal equity offering; underpricing; underperformance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|